Valuable broadleaved forests in Europe - Spiecker, Heinrich (Research report (European Forest Institute), 2009)
Valuable broadleaved tree species offer options for increasing ecological, economic and social values and contribute to sustainability of forestry in Europe and other parts of the world. They increase the production of high quality timber while maintaining and improving environmental values such as biodiversity, stability and naturalness and the beauty of the landscape. The high diversity in sites, ownership, economic and socio-cultural conditions in Europe require different strategies adapted to the local needs.